The Dynamics of Organizational Performance: Deciphering Belief Systems, Diagnostic Controls, and Interactive Management - Chairunisa, Mariyam; Putra, Yananto Mihadi; Gani, Ibrahim Musa (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2022)
The performance of an organization can be influenced by the management control systems it adopts. This study aims to investigate the impact of such systems on organizational performance, with a particular focus on the role of innovation as a mediator. The research draws on the Contingency and Levers of Control theories and uses data collected from manufacturing companies in the West Java Area through post, electronic mail, and direct surveys. The data collected from managers and assistant managers was analyzed using PLS Structural Equation Modeling (SEM). The study found that a management control system that includes a trust system and an interactive control system has a positive and significant effect on innovation and, ultimately, on organizational performance. However, the diagnostic control system does not significantly influence innovation. It is important to note that this study only looks at the innovation capability construct.